Sex-specific variations in global DNA methylation levels with age: a population-based exploratory study from North India - Kaushik, Anshika; Chaudhary, Vineet; Longkumer, Imnameren; Saraswathy, Kallur Nava; Jain, Sonal (Frontiers in Genetics, 2023)
Purpose: Aging is one of the most important risk factors for a number of human diseases. Epigenetic alterations, including changes in DNA methylation patterns, have been reported to be one of the hallmarks of aging. Being a malleable process, the role of site-specific DNA methylation in aging is being extensively investigated; however, much less attention has been given to alterations in global DNA methylation with aging at the population level. The present study aims to explore overall and sex-specific variations in global DNA methylation patterns with age. Methods: A total of 1127 adult individuals (792 females) aged 30-75 years belonging to Haryana, North India, were recruited. Socio-demographic data was collected using a pretested interview schedule. Global DNA methylation analysis, of peripheral blood leucocyte (PBL) DNA, was performed using the ELISA-based colorimetric technique. Results: Though the overall correlation analysis revealed a weak inverse trend between global DNA methylation and age, the adjusted regression model showed no significant association between global DNA methylation and age. In age-stratified analysis, global DNA methylation levels were found to be fairly stable until 60 years of age, followed by a decline in the above-60 age group. Further, no significant difference in DNA patterns methylation pattern was observed between males and females. Conclusion: Overall, the study suggests a lack of association between global DNA methylation and age, especially until 60 years of age, and a similar DNA methylation pattern between males and females with respect to age.